Managing in Tough Times: Building Your Assets by Volunteering and Networking - Selena Garrison; Michael S. Gutter; Lynda Spence (EDIS)
FCS7239, a 5-page fact sheet by Selena Garrison, Michael S. Gutter, and Lynda Spence, describes strategies job seekers can use to market themselves to their communities and potential employers by volunteering and using online networking resources. Published by the UF Department of Family Youth and Community Sciences, October 2009.